1992
DOI: 10.1093/geronj/47.3.p199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perceived Responsibility on Help-Seeking Decisions Among Elderly Persons

Abstract: This study sought to clarify why elderly adults underutilize mental health services. One hundred ten elderly individuals were asked to imagine experiencing symptoms described in a vignette and to appraise their responsibility for the problem and for its solution, their willingness to seek help, and their preference among sources of help. Results indicated that perception of problems as either medical or psychological significantly affected how elders appraised responsibility. Although attributions were unrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 0 publications
1
23
1
Order By: Relevance
“…Additionally, like studies examining health-seeking for mental problems (Ray et al, 1992;Angermeyer et al, 1999), results of this study showed that higher intentions to seek help from professional sources were reported for problems having more severe consequences (i.e. the inability to remember the names of relatives in the scenarios presented).…”
Section: Discussionsupporting
confidence: 49%
“…Additionally, like studies examining health-seeking for mental problems (Ray et al, 1992;Angermeyer et al, 1999), results of this study showed that higher intentions to seek help from professional sources were reported for problems having more severe consequences (i.e. the inability to remember the names of relatives in the scenarios presented).…”
Section: Discussionsupporting
confidence: 49%
“…This has been observed for other conditions (Ray, Raciti, & MacLean, 1992) and may result from differential attributions of responsibility (Kroska & Harkness, 2006). For example, Weiner, Perry, and Magnusson (1988) compared study participants' perceptions of individuals with conditions for which their own behavior was believed to be a contributory factor (i.e., AIDS and obesity) with those of individuals believed to have little or no role in the onset of their condition (i.e., Parkinson's disease and multiple sclerosis).…”
Section: Research Related To Stigma and The MCI Labelmentioning
confidence: 55%
“…Greater Breadth scores were found for older adults, higher Biases and Range of Knowledge scores were found for younger adults, and no age effects were found for Openness, each based upon the 1991-2000 comparison. This suggests that older adults do not, relative to younger adults, necessarily hold limited or inaccurate attributions about the causes of mental illness, as suggested by the literature (e.g., Ray et al, 1992;Robb et al, 2003). In this study (re: Range of Knowledge), younger adults viewed children leaving home, isolation from family, sexual difficulties, and the death of a close friend as problems worthy of professional input to a greater degree than did older adults.…”
Section: Age Cohort Effects In Mental Health Perceptionsmentioning
confidence: 58%